Undiagnosed type 2 diabetes during pregnancy is associated with increased perinatal mortality: a large population‐based cohort study in Ontario, Canada. Issue 10 (16th February 2020) - Lee, D.; Booth, G. L.; Ray, J. G.; Ling, V.; Feig, D. S.
Abstract: Aim: To compare perinatal outcomes in women with undiagnosed diabetes with gestational diabetes alone, pre‐existing diabetes and women without diabetes, and to identify risk factors which distinguish them from women with gestational diabetes alone. Methods: This population‐based cohort study included administrative data on all women who gave birth in Ontario, Canada, during 2002–2015. Maternal/neonatal outcomes were compared across groups using logistic regression, adjusting for confounders. A nested case control study compared women with undiagnosed type 2 diabetes with women with gestational diabetes alone to determine risk factors that would help identify these women. Results: Among 995 990 women, 68 163 had gestational diabetes (6.8%) and, of those women with gestational diabetes, 1772 had undiagnosed type 2 diabetes (2.6%). Those with undiagnosed type 2 diabetes were more likely to be older, from a lower income area, have parity > 3 and BMI ≥ 30 kg/m 2 compared with gestational diabetes alone. Infants had a higher risk of perinatal mortality (OR 2.3 [1.6–3.4]), preterm birth (OR 2.6 [2.3–2.9]), congenital anomalies (OR 2.1 [1.7–2.5]), neonatal intensive care unit admission (OR 3.1 [2.8–3.5]) and neonatal hypoglycaemia (OR 406.0 [357–461]), which were similar to women with pre‐existing diabetes. The strongest predictive risk factors included early gestational diabetes diagnosis, previous gestational diabetes and chronic hypertension. Conclusions: Women diagnosed with gestational diabetes who develop diabetes within 1 year postpartum are at higher risk of adverse pregnancy outcomes, including perinatal mortality. This highlights the need for earlier diagnosis, preferably pre‐pregnancy, and more aggressive treatment and surveillance of suspected type 2 diabetes during pregnancy. What's new?: While it is suspected that several women with a diagnosis of gestational diabetes have undiagnosed type 2 diabetes, no study has followed these women through the first year postpartum to see the prevalence of actual undiagnosed type 2 diabetes during pregnancy and the maternal and neonatal outcomes of these women. This study found that 26 per 1000 women with gestational diabetes had undiagnosed type 2 diabetes. Infants of women with undiagnosed type 2 diabetes had a higher risk of adverse pregnancy outcomes including perinatal mortality compared with women with gestational diabetes alone. This study highlights the need for earlier diagnosis, preferably pre‐pregnancy, and more aggressive treatment and surveillance of suspected type 2 diabetes cases during pregnancy.